Movement patterns of Sanderling (Calidris alba) in the East Asian-Australasian Flyway and a comparison of methods for identification of crucial areas for conservation. (1st June 2016) - Lisovski, Simeon; Gosbell, Ken; Christie, Maureen; Hoye, Bethany J.; Klaassen, Marcel; Stewart, Iain D.; Taysom, Alice J.; Minton, Clive
Abstract: Worldwide, most populations of migratory shorebirds are in jeopardy, none more so than those of the East Asian—Australasian Flyway (EAAF). In order to preserve these highly mobile species a detailed understanding of their use of feeding and resting sites along the flyway is required. In this study we used light-level geolocators and new analytical tools to reveal individual breeding locations and migration routes of 13 Sanderlings ( Calidris alba ) that spend their non-breeding season in South Australia. We then used these individual migration routes to identify the timing and location of important stopping areas and compared this with assessments based on resightings of leg-flagged birds and count data. During both northward and southward migration, Sanderlings were found to make extensive use of five main areas of the Chinese coastline, the Yellow Sea and the northern end of the Sakhalin Peninsula. Insights gained from the individual migration routes highlight inherent biases in using only count and resighting data to identify important feeding and resting sites along the Flyway. These findings suggest that data on individual movements may be crucial to effective conservation planning of shorebirds in the EAAF and elsewhere in the world.